The National Social Distance Study: Ten Years Later1. Issue 3 (23rd August 2013) - Parrillo, Vincent N.; Donoghue, Christopher
Abstract : The Bogardus social distance scale, which measures the level of acceptance that Americans feel toward members of the most common ethnic and racial groups in the United States, was administered six times nationally between 1920 and 2001. Replicating the most recent study with its revised list of ethnic and racial groups, the authors of this study analyzed a stratified random sample of 3, 166 college students, making it the largest national social distance study ever conducted. The findings indicate an increase since 2001 in the mean level of social distance toward all ethnic groups, as well as in the spread between the groups with the highest and lowest levels of social distance. Further, a consistency between studies in group preferences reaffirms the relevance of the similarity‐attraction bond in accepting those who are racially and culturally different. Mean comparisons and analysis of variance tests also showed that gender, birthplace of respondents and/or their parents, race, and year in college are all significant indicators of the level of social distance toward groups.